The Spectrum, Tendency and Predictive Value of PIK3CA Mutation in Chinese Colorectal Cancer Patients - Fu, Xinhui; Lin, Hanjie; Fan, Xinjuan; Zhu, Yaxi; Wang, Chao; Chen, Zhiting; Tan, Xiaoli; Huang, Jinglin; Cai, Yacheng; Huang, Yan (Frontiers in Oncology, 2021)
Background PIK3CA is a high-frequency mutation gene in colorectal cancer, while its prognostic value remains unclear. This study evaluated the mutation tendency, spectrum, prognosis power and predictive power in cetuximab treatment of PIK3CA in Chinese CRC cohort. Methods The PIK3CA exon 9 and 20 status of 5763 CRC patients was detected with Sanger sequencing and a high-resolution melting test. Clinicopathological characteristics of 5733 patients were analyzed. Kaplan-Meier method and nomogram were used to evaluate the overall survival curve and disease recurrence, respectively. Results Fifty-eight types of mutations in 13.4% (771/5733) of the patients were detected. From 2014 to 2018, the mutation rate of PIK3CA increased from 11.0% to 13.5%. At stage IV, exon 20 mutated patients suffered shorter overall survival time than wild-type patients (multivariate COX regression analysis, HR = 2.72, 95% CIs = 1.47-5.09; p-value = 0.012). At stage III, PIK3CA mutated patients were more likely to relapse (multivariate Logistic regression analysis, exon 9: OR = 2.54, 95% CI = 1.34-4.73, p = 0.003; exon 20: OR = 3.89, 95% CI = 1.66-9.10, p = 0.002). The concordance index of the nomogram for predicting the recurrence risk of stage III patients was 0.685. After cetuximab treatment, the median PFS of PIK3CA exon 9 wild-type patients (n = 9) and mutant patients (n = 5) did not reach a significant difference (3.6 months vs. 2.3 months, Log-rank test, p-value = 0.513). Conclusions We found that PIK3CA mutation was an adverse predictive marker for the overall survival of stage IV patients and recurrence of stage III patients, respectively. Further more, we suggested that PIK3CA exon 9 mutations are not negative predictors of cetuximab treatment in KRAS, NRAS, and BRAF wild-type mCRC patients.